Vertical coupling for silicon nitride waveguides using silicon grating couplers and transitions - Xiao, Zhe (2013)
Fiber to silicon nitride waveguides coupling is achieved using silicon grating coupler with a transition. Two optimized couplers are designed for TE and TM mode excitation, achieving over 55% efficiency. Fabrication issues are also discussed.